Optimization of the flotation circuit of a gold-pyrite processing plant by computer simulation - Tabell, Victor Oliver L.
Froth flotation is a process widely used for concentrating valuable minerals from the gangue through the manipulation of mineral surface properties. In Itogon, Benguet, a flotation circuit has been put up that can generate free gold and gold-bearing sulphides as concentrates from native ore. However, the existing circuit still requires substantial optimization. The traditional optimization process can be extensively arduous and costly. Understanding the effect of varying one parameter to the final concentrate can be easily achieved, but factoring in the effect of several parameters at the same time makes the optimization process challenging. This study proposes the use of computer simulation to predict flotation performance; thereby, allowing a faster method of optimization. By varying the pulp density, testing different circuit configurations and introducing a regrind-classification stage, the study was able to recommend improvements to the existing flotation circuit in Benguet. The simulation results showed that shifting to a lower pulp density in all flotation stages helped increase concentrate grade without sacrificing the recovery. The simulation also showed that introducing a classifier (i.e. hydrocyclone) prior to the cleaner stage generally improved gold recovery in the final concentrate due to the flotation of finer particle sizes. Also, results showed that removal of the scavenger bank and one cleaner cell does not significantly affect the final concentrate grade and recovery. Through the aid of several simulations, the study was able to optimize the existing flotation circuit in Benguet, achieving maximum recoveries of 97% and 95% for gold and pyrite, respectively.